"My youth, I call the shots": A qualitative examination of university students' perspectives on life transition and identity development in China. (November 2018) - Yuan, Rui; Ngai, Steven Sek-yum
Abstract: There is a dearth of empirical evidence in Chinese societies to explore young people's identity development process in life transition from adolescence to adulthood. Using a qualitative methodology, this study conducted in-depth interviews with 18 Chinese university students in Shanghai, China. Participants had a mean age of 20.68 years (SD = 2.13). The sample consisted of eight men and ten women. Thematic analysis focusing on identifiable themes and patterns of experience and behavior was used in this study. Results indicated that in planning their lives and experimenting with new social roles, young people actively generated resources embedded in family relationships, peer groups, and other institutional networks. They recognized the changing family dynamics, enhanced peer networks, and received institutional support. Accordingly, they constructed a self that was more filial to parents, more exploratory toward life opportunities, and more oriented in a career than their previous selves. Highlights: In-depth interviews were conducted. Family relationships, peer groups, and other institutional networks were critical to identity development. Young people constructed a self that was more filial to parents, more exploratory toward life opportunities, and more oriented in a career.